Possibility of the application of the computational intelligence in the production of superhard materials. Report 2 - Tavares, L.O.; Vianna, W.S.; Bobrovnitchii, G.S.; Skury, A.L.D.; Rangel, J.J.A. (Сверхтвердые материалы, 2012)
A new system to control a 630-ton and a 2500-ton presses has been developed. By using this system it has been made possible to define new parameters related to pressure and temperature and the influence of certain factors on them. Furthermore, the new system has been shown to indicate that other parameters, such as height of the gasket formed, electrical resistance of the reaction cell, and the frequency of activation of the pump or multiplier, can serve as important indicators of the improvement of superhard material production technologies, implementing the Computational Intelligence.